2018
DOI: 10.1080/03004279.2018.1445484
|View full text |Cite
|
Sign up to set email alerts
|

Early childhood education for sustainability: origins and inspirations in the work of John Dewey

Abstract: Early childhood education for sustainability: origins and inspirations in the work of John Dewey In this article, the work of John Dewey is recontextualised and proposed as a basis for contemporary early childhood education for sustainability (ECEfS). Five key themes are explored: experiential learning; curiosity and critical thinking; children's experiences in nature; democracy and participation; and classroom as community. In each case, claims are made through aligning the work of Dewey with exemplars from c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 21 publications
0
13
0
5
Order By: Relevance
“…According to Dewey, novel insights emerge when experience is integrated with existing knowledge through a process of learner-initiated inquiry (Luff, 2018). Dewey also believed that individuals live within the world, are in constant interaction or transaction with it (Williams, 2017) and can understand the world through an inquiry involving multiple individuals (Luff, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…According to Dewey, novel insights emerge when experience is integrated with existing knowledge through a process of learner-initiated inquiry (Luff, 2018). Dewey also believed that individuals live within the world, are in constant interaction or transaction with it (Williams, 2017) and can understand the world through an inquiry involving multiple individuals (Luff, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Within outdoor education literature, John Dewey's foundational contribution to the movement of experiential learning (Dewey, 1938) has been studied by several researchers (e.g., Luff, 2018;Moss & Normore, 2006). For decades, researchers of outdoor learning have shown that in the USA, field trips and excursions were a great contribution to students educational development (NASSP, 1941) with multiple benefits, and it was even stated that "good learning and the outdoors are inseparable" (NASSP, 1957, p. 141).…”
Section: Brief Notes About Outdoor and Environmental Education In Certain North American Countriesmentioning
confidence: 99%
“…While it is true that sustainable development deals with abstract and complex relationships that are especially difficult for children [24], many authors have stressed the importance of environmental education, and some say that education in environmental sustainability should start in childhood [18,[25][26][27][28][29]. In addition, early childhood education could play an essential role in sustainable practice, as it is considered to be a period of time when children's main attitudes and values are established for the first time [27,[30][31][32][33]. According to Davis [12], the experiences provided for young children are influential to their present and future beliefs, values, well-being, and individual and social development.…”
Section: Education For Sustainable Development In Early Childhoodmentioning
confidence: 99%
“…In terms of early childhood sustainability education, attention to experiential learning is central and lies at the heart of early childhood education [33]. Learning through games and active exploration of the environment has been considered a characteristic of early learning [34].…”
Section: Education For Sustainable Development In Early Childhoodmentioning
confidence: 99%
See 1 more Smart Citation